Precision Strikes on HIV: CRISPR/Cas9-Mediated Disruption of CCR5 and CXCR4 to Block Viral Entry and Establish Cellular Immunity - Sandhu, Abdul Sami; Anas, Muhammad; Eisha,; Shoukat, Saba; Talha, Muhammad; Chorahi, Muhammad Umer; Arif, Muhammad Irfan; Arbab, Qurat ul Ain (Indus Journal of Bioscience Research, 2025)
As of 2023, there were about 39 million people living with HIV, making it a persistent threat to global health. Lifelong treatment is required because antiretroviral therapy (ART) suppresses viral replication but does not eliminate latent reservoirs. By focusing on host co-receptors CCR5 and CXCR4, which are essential for HIV entry into CD4+ T cells and macrophages, the CRISPR/Cas9 gene-editing system provides a novel strategy. The disruption of CCR5 and CXCR4 by CRISPR/Cas9 to stop viral entry and build cellular immunity is thoroughly examined in this review. The design of guide RNAs, delivery methods, and off-target mitigation techniques are among the molecular mechanisms of CRISPR/Cas9 that we examine. While CXCR4 editing presents difficulties because of its wider physiological functions, preclinical research shows that CCR5 knockout in T cells and hematopoietic stem cells (HSCs) confers strong HIV resistance. Safe engraftment and lower viral loads are promising outcomes of clinical trials that target CCR5. We also talk about new technologies like base editing, scalability, viral escape risks, and ethical issues. This review identifies important barriers for clinical translation while highlighting the potential of CRISPR/Cas9 to provide a functional HIV cure.